A Review of Legal Protection for Workers with Fixed Term Employment Contracts Under Law No. 13 of 2003 on Manpower - Dalimunthe, Nikmah; pulungan, Ro’fat ja’far Al-hadidi; Anwar, Khahmilul; Haryono, Daffa Naufal; Siregar, Dina Aulia Rahmi; Harahap, Aisyah; Harahap, Hafni Meylani (The Future of Education Journal, 2025)
This study focuses on how the law protects contract workers based on the provisions of Law No. 13 of 2003 concerning Manpower. Using a normative approach based on legislation and conceptual methods, this study draws on secondary data such as Law No. 13 of 2003, Government Regulation No. 35 of 2021, legal references, and scientific works. The findings indicate that labor regulations in Indonesia provide fairly comprehensive protection for PKWT workers, including BPJS membership, the right to fair wages, occupational health and safety, and freedom of association. However, there is a clear discrepancy between the legal norm (das sollen) and its implementation (das sein). The main challenges that arise include diverse interpretations of the term “de jure” so that changes in employment status do not proceed as they should, unclear responsibilities in the outsourcing system, weak labor supervision due to limited resources and low compliance among business actors, and low legal understanding and access to justice for workers. Although the available regulations are quite comprehensive, the effectiveness of protection for PKWT workers is still not optimal, requiring significant improvements both normatively and institutionally, particularly regarding the consistency of law enforcement, increasing the capacity of supervisors, improving mechanisms for handling violations, and strengthening legal education for workers.